2006
DOI: 10.1086/508649
|View full text |Cite
|
Sign up to set email alerts
|

Debris Disk Evolution around A Stars

Abstract: We report 24 and/or 70 µm measurements of ∼160 A-type main-sequence stars using the Multiband Imaging Photometer for Spitzer (MIPS). Their ages range from 5 to 850 Myr based on estimates from the literature (cluster or moving group associations) or from the H-R diagram and isochrones. The thermal infrared excess is identified by comparing the deviation (∼3% and ∼15% at the 1-σ level at 24 and 70 µm, respectively) between the measurements and the synthetic Kurucz photospheric predictions. Stars showing excess i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
576
6
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(640 citation statements)
references
References 38 publications
56
576
6
2
Order By: Relevance
“…Stars with an independent age measurement from membership in a moving group (as detailed in Table 1) are plotted twice, once as an empty green circle with error bars indicating the results of the Bayesian analysis and again as a filled green circle indicating the age of the moving group, which we adopt as the final age for that star. There is good agreement between our work and Su et al (2006) for stars that Su et al (2006) flag as older than 100 Myr, but below that age our Bayesian analysis finds systematically older ages as expected. For the moving group stars, since the Bayesian analysis of photometry can only place a star in the first third of its main-sequence lifetime, additional information is needed to age-date young stars with greater accuracy.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Stars with an independent age measurement from membership in a moving group (as detailed in Table 1) are plotted twice, once as an empty green circle with error bars indicating the results of the Bayesian analysis and again as a filled green circle indicating the age of the moving group, which we adopt as the final age for that star. There is good agreement between our work and Su et al (2006) for stars that Su et al (2006) flag as older than 100 Myr, but below that age our Bayesian analysis finds systematically older ages as expected. For the moving group stars, since the Bayesian analysis of photometry can only place a star in the first third of its main-sequence lifetime, additional information is needed to age-date young stars with greater accuracy.…”
Section: Discussionsupporting
confidence: 82%
“…For the ages derived by our Bayesian analysis, we find good agreement for stars which Su et al (2006) determine to be older than 100 Myr. Stars that Su et al (2006) find to be younger than 100 Myr show a systematic disagreement, with the median of our Bayesian age distribution significantly older than the single age found by Su et al (2006). This is as we would expect, since most movement across the color-magnitude diagram happens in the final two-thirds of a star's main-sequence lifetime, so older stars can be age-dated more definitively while younger stars can be anywhere in the first third of their main-sequence lifetimes.…”
Section: Comparison With Previous Agesmentioning
confidence: 55%
See 1 more Smart Citation
“…It was later shown that both the scatter seen in the observations and the decay in emission levels could be explained by the steady state erosion of extrasolar Kuiper belts (Wyatt et al 2007b); the level observed simply reflects the initial mass in the belt and its distance from the star, which was far enough that the emission was generally cold and so also explained the observations at 70 µm toward the same stars (Su et al 2006). The same issue affected the interpretation of Sun-like stars, since it was found that the emission spectrum for the majority of these stars was rising toward longer wavelengths implying that the 24 µm emission arises in a belt far enough from the star (> 10 au) to be explained by steady state processes (Carpenter et al 2009).…”
Section: Photometric Fluxesmentioning
confidence: 93%
“…Also in Figure 4 are plotted model extrapolations for dusty A-type stars from Su et al (2006), as their current dust properties would appear if the host stars were evolved into cool white dwarfs with parameters similar to G29-38. To begin, the inferred orbital radii of the dust components on the main sequence were expanded by a factor r wd /rms = Mms/M wd ≈ 3.5, appropriate for G29-38 and a representative value for A stars based on the initial-to-final mass relations (e.g.…”
Section: Projections Of Dusty A-type Starsmentioning
confidence: 99%